KARAKTERISTIK PEMERINTAH DAERAH TERHADAP LEMBAGA KEUANGAN - Mukuan, Danny (JURNAL ADMINISTRASI BISNIS, 2017)
Local financial problem is one of the main concern in this research. The local government has important role in order to control and manage local finance, therefore in â€œUU No. 33 Tahun 2004 tentang Perimbangan Keuangan Pusat dan Daerahâ€ stated that implementation of regional autonomy through provision of resource based on Central Government decision, â€œdesentralisasiâ€, â€œdekonsentrasiâ€ and â€œtugas pembantuanâ€, the financial balancing between Central Government and local Government has to be regulated based on clear competency, role and duty in the government.